(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article is a study of the role of wordplay as a means of attraction of clients in the structure of commercial names, of the structural and semantic-associative features of wordplay in ergonymy. It distinguishes and analyzes models of company names of the Ternopil region of Ukraine, which are formed by means of different types of wordplay.